Sonographic Comparison between PCOS, Hyperstimulated Ovaries and Hyperreactio Luteinalis - Usman Ihsan, Syed Aamir Gilani, Muhammad Kaleem Akhter, Humiara Yousaf, Anam Iftikhar, Nadia Majeed, Mubashir Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Polycystic Ovarian Syndrome (PCOS) is a highly prevalent endocrinological disorder of females characterized by hirsutism, infertility and bilaterally enlarged multicystic ovaries.It is also a risk factor for development of Ovarian Hyperstimulation Syndrome (OHSS) and Hyperreatcio luteinalis (HL). Aim: To identify the value of ultrasonography in distinguishing these three interlinked pathologies and highlight the need for additional relevant investigations to make confirmatory diagnosis of any of them. Method: We conducted a systematic search by using Google Scholar and PubMed as search engines to retrieve all the available English-language literature on ultrasonographic findings of PCOS, OHSS and HL published from 2016 to 2021 while following PRISMA Statement. Results: Out of 316 articles retrieved ,only 9 articles were found that met the preset inclusion and exclusion criteria and of which there were 8 case reports and 1 narrative review. Conclusion: PCOS, OHSS and HL are interrelated ovarian morphological abnormalities with almost same ultrasonographic features.Correlation of these features with other relevant lab investigations and clinical parameters is therefore necessary to make an individual diagnosis out of them.